2010
DOI: 10.1016/s1734-1140(10)70304-2
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase (NNMT) and 1-methylnicotinamide (MNA) in experimental hepatitis induced by concanavalin A in the mouse

Abstract: Nicotinamide N-methyltransferase (NNMT), which converts nicotinamide (NA) to 1-methylnicotinamide (MNA), is up-regulated in the cirrhotic liver. Because MNA displays PGI(2)-dependent anti-inflammatory effects, the up-regulation of NNMT may play a regulatory role in liver inflammation. In the present work, we analyzed changes in NNMT activity in the liver and concomitant changes in the concentration of endogenous MNA in plasma in T-cell dependent hepatitis induced by concanavalin A (ConA) in BALB/c mice. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…Such a cytoprotective effect for NNMT is not without precedent. A recent study has shown that NNMT expression is induced in both the cirrhotic liver and experimental hepatitis as a hepatoprotective mechanism in response to the underlying pathogenic process, and that this is mediated by elevated MeN production [41]. Our results also suggest that the overexpression of NNMT in a variety of cancers may be a contributory factor to their accelerated growth, raising the possibility of using NNMT inhibitors for the treatment of cancer.…”
Section: Nnmt Expression and Men Protect Against The Toxicity Of Inhisupporting
confidence: 67%
“…Such a cytoprotective effect for NNMT is not without precedent. A recent study has shown that NNMT expression is induced in both the cirrhotic liver and experimental hepatitis as a hepatoprotective mechanism in response to the underlying pathogenic process, and that this is mediated by elevated MeN production [41]. Our results also suggest that the overexpression of NNMT in a variety of cancers may be a contributory factor to their accelerated growth, raising the possibility of using NNMT inhibitors for the treatment of cancer.…”
Section: Nnmt Expression and Men Protect Against The Toxicity Of Inhisupporting
confidence: 67%
“…Accordingly, increase in the concentration of MNA in ConA-induced hepatitis may reflect an endogenous defensive mechanism limiting the inflammatory processes along the progression of liver injury by a PGI 2 -dependent pathway. In fact, hepatoprotective action of exogenous MNA in ConA-induced hepatitis was reversed by a prostacyclin receptor antagonist [35]. We also demonstrated that carboprostacyclin (cPGI 2 ) reduced the production of IFNS, IL-4, TNFα in spleen cells (data not published).…”
Section: Discussionmentioning
confidence: 79%
“…This compound was found to have anti-thrombotic ( Chlopicki et al, 2007 ), vasoprotective ( Bartu ś et al, 2008 ), gastroprotective ( Brzozowski et al, 2008 ), antiinflammatory ( Sternak et al, 2010 ), and neuroprotective ( Milani et al, 2013 ) properties. It could be interesting to speculate whether N1-methylnicotinamide exerts a cytoprotective effect against antineoplastic compounds in cancer cells.…”
Section: Discussionmentioning
confidence: 99%